Differences in teacher's perspective on academic engagement among students of Orang Asli and non-Orang Asli students / Mohd Azizul Sulaiman ... [et al.] - Sulaiman, Mohd Azizul; Mohd Azmi, Nor Farhana; Ridzuan, Arifi; Aminuddin, Azwan Shah; Saini, Norhana Aini (Universiti Teknologi MARA Cawangan Pahang, 2020)
The standard of education among the Orang Asli people as an indigenous ethnic in Malaysia is still at a low level. Much of the Orang Asli people receive formal education only at the primary level. However, there is a significant trend where most students who completed their primary education will drop out from secondary school. Hence, only marginal amount of them have been successful in advancing their higher education in tertiary institutions. Such problems are commonly associated with several factors, including students' attitudes, awareness among parents about education, local culture, school leadership, school environment, and problems related to the teaching and learning process. Academic engagement seems to serve as an important social signal, eliciting supportive reciprocal reactions. Besides that, engagement is also a good forecaster of children's long-term academic achievement (Skinner et al., 1998) and their eventual completion of school (Connell, Spencer & Aber, 1994). Relating back to the case scenario, the academic engagement among Orang Asli is knowingly poor. Hence, if they were being introduced with the curriculum and pedagogy (of learning) which are unsuitable with their interests, or if they are unrelated with their daily lives, these could be one of the reasons for them to be less interested to study or to focus in class (Haslinda, Lilia & Zanaton, 2015). For better understanding of this problem, a specific research will be carried out to study the academic engagement of Orang Asli students in Taman Negara Pahang. The objective of this study is to explore teacher's perspective on academic engagement among students of Orang Asli, an indigenous minority community in Malaysia. Differences of perceptions towards academic engagement among teachers who teach students of Orang Asli and non-Orang Asli students also explored. This survey study conducted among teachers who teach both students in Pahang School. The research focused on teacher perspectives based on the questions: 1. What are the level of involvement in academic engagement among Orang Asli students and non-Orang Asli students. 2. Is there any differences in teacher's perspective on academic engagement between Orang Asli students and non-Orang Asli students? A set of questionnaires distributed among teachers as samples. Data was analyzed using descriptive statistics. This study will hopefully give implication on the importance of teacher's role to enhance academic engagement among students of Orang Asli and normal students. The implications of the problems and teachers' attitudes are significantly associated with degrading interest among students on education, issues of attendance and students' academic performance.